Systemic inflammatory response index as a predictor of inflammation and mortality in hemodialysis patients - Esen, Rengin; Kiliç, Jehat; Karabay, Umut; Yüksel, Enver; Daniş, Ramazan (Springernature, 2026)
Introduction Chronic kidney disease is a global health problem with high mortality among hemodialysis patients. We evaluated the prognostic value of the systemic inflammatory response index (SIRI) in this population. Material method This retrospective cross-sectional study included 340 adult patients undergoing maintenance hemodialysis for more than three months (2015-2022). Demographic and clinical data, comorbidities, and laboratory parameters were retrieved from electronic records. The Systemic Inflammatory Response Index (SIRI) was calculated as (neutrophil & times; monocyte) / lymphocyte count, and patients were categorized into low (< 1.54) and high (>= 1.54) SIRI groups. Results A total of 340 hemodialysis patients were included (mean age 55.2 +/- 17.4 years; 52.6% female). Patients in the high-SIRI group were significantly older and more frequently female than those in the low-SIRI group. Diabetes mellitus was more prevalent, whereas obstructive and polycystic kidney diseases were less common among high-SIRI patients. Higher SIRI levels were associated with increased neutrophils, monocytes, white blood cell count, NLR, MLR, CRP, and CAR, along with lower lymphocyte counts, albumin, Kt/V, and PTH levels (all p < 0.05). Although 5-year overall survival was numerically lower in the high-SIRI group, the difference was not statistically significant. In multivariable Cox regression, only age and male sex independently predicted mortality. Conclusion High SIRI was associated with older age, increased inflammatory burden, and poorer dialysis adequacy but not with mortality. Age and male sex independently predicted death. SIRI reflects inflammation in hemodialysis patients but has limited independent prognostic value.
Keywords: SIRI; Mortality; Inflammation; NLR; MLR; CRP; Albumin; CAR; Dry weight; Kt/V; Hemodialysis